High-precision modulation of a safety-critical cyber-physical system : control synthesis and experimental validation - Li, Yutong (2019)
As a typical safety-critical cyber-physical system, the brake-by-wire system, which provides improved control and enhanced performance, shows promise as an automotive braking scheme. In addition, the BBW system can be incorporated into all types of vehicles, including conventional vehicle with an internal combustion engine, electrified vehicles, and intelligent vehicles. However, the high cost and complexity of existing BBW systems limit their usage. In this paper, we consider a novel BBW system that we have developed, which has the advantages of having a simple structure and low cost. To enhance control accuracy of hydraulic pressure modulation and reduce noise, two pressure modulation methods, namely, the hydraulic pump based pressure modulation (HPBPM) and the close-loop pressure-difference-limiting (CLPDL) modulation, were proposed. So as to demonstrate the performance of the proposed approach, hardware-in-the-loop (HiL) experiments were conducted. The experimental results indicated that the proposed BBW system, which incorporates the CLPDL control method, appears to be a promising system in terms of overall performance, including control performance, noise reduction, and system simplification.